Reduced Risk of Sepsis and Related Mortality in Chronic Kidney Disease Patients on Xanthine Oxidase Inhibitors: A National Cohort Study - Yang, Huang-Yu; Hsu, Yun-Shiuan Olivia; Lee, Tao Han; Wu, Chao-Yi; Tsai, Chung-Ying; Chou, Li-Fang; Tu, Hui-Tzu; Huang, Yu-Tung; Chang, Shang-Hung; Yen, Chieh-Li; Hsieh, Meng-Hsuan; Lee, Cheng-Chia; et al. (Frontiers in Medicine, 2022)
Background Advanced chronic kidney disease (CKD) patients are at higher risk of sepsis-related mortality following infection and bacteremia. Interestingly, the urate-lowering febuxostat and allopurinol, both xanthine oxidase inhibitors (XOis), have been suggested to influence the sepsis course in animal studies. In this study, we aim to investigate the relationship between XOis and infection/sepsis risk in pre-dialysis population. Methods Pre-dialysis stage 5 CKD patients with gout were identified through the National Health Insurance Research Database (NHIRD) in Taiwan from 2012 to 2016. Outcomes were also compared with national data. Results In our nationwide, population-based cohort study, 12,786 eligible pre-dialysis stage 5 CKD patients were enrolled. Compared to non-users, febuxostat users and allopurinol users were associated with reduced sepsis/infection risk (hazard ratio (HR), 0.93; 95% confidence interval (CI), 0.87-0.99; P=0.0324 vs. HR, 0.92; 95% CI, 0.86-0.99; P=0.0163). Significant sepsis/infection-related mortality risk reduction was associated with febuxostat use (HR, 0.68; 95% CI, 0.52-0.87). Subgroup analysis demonstrated preference of febuxostat over allopurinol in sepsis/infection-related mortality among patients younger than 65 years of age, stain users, nonsteroidal anti-inflammatory drug non-users, and non-diabetics. There was no significant difference in major adverse cardiac and cerebrovascular event (MACCE) risk between users and non-users while reduced risk of all-cause mortality was observed for XOi users. Conclusions. Use of XOi in pre-dialysis stage 5 CKD patients may be associated with reduced risk of sepsis/infection and their related mortality without increased MACCE and overall mortality.